Investigating the Therapeutic Effect of Combined Colon Clear and Cupping Therapy on Idiopathic Skin Pathology: A Prospective Study - Abdullah M Nasrat; Salwa AM Nasrat; Randa M Nasrat; Mohammad M Nasrat; Sanaa Y Babiker (Disease and Health: Research Developments Vol. 4, 2025)
The complex spectrum of inflammatory skin diseases is ever-expanding and evolving, particularly in psoriasis, idiopathic eczema and atopic dermatitis. The study aimed at demonstration of idiopathic skin pathology; influence of Helicobacter pylori and therapeutic effect of combined colon clear with cupping therapy. Idiopathic eczema is an atopic inflammatory skin disease which has got mostly a chronic relapsing course with seasonal variation and marked influence of emotional stress. The complex spectrum of inflammatory skin diseases is ever expanding and evolving particularly in psoriasis, idiopathic eczema and atopic dermatitis. The etiology of these inflammatory atopic dermato-pathological disorders is still obscure but it is basically autoimmune triggered and maintained by an aberrant response of the skin immune system cells. Pro-inflammatory cytokines play a pivot role in the pathogenesis of immune skin pathologies. This prospective study done in Balghsoon Clinics in Jeddah, Saudi Arabia between October 2011 and May 2013. H. pylori could migrate or get forced to migrate to the colon leading to accumulation of profuse toxic amounts of ammonia unopposed or buffered by any acidity. The association of H. pylori with autoimmune disorders and chronic idiopathic dermatitis was sufficiently reported. The role played by the increased mucosal production of inflammatory mediators (cytokines) induced by H. pylori was also clearly illustrated. Antibiotics are seldom effective against extra-gastric H. pylori strains. A potent natural purgative is the only measure to eradicate H. pylori strains migrated to the colon. Elimination of toxic metabolites and inflammatory mediators from the body is a challenge which is only feasible via seroclearance blood-let out cupping therapy. The management of atopic dermatitis primarily focuses on restoring the skin barrier, controlling itch, and reducing inflammation. Seven patients with atopic dermatitis, seven with idiopathic eczema and seven with psoriasis were randomly included in the study on the basis of being newly discovered, not starting any definitive treatment and having a frank history of H. pylori dyspepsia which was proved by sensitive specific tests. All patients underwent colon clear employing the potent natural senna purge which was followed in five days by a session of blood-let out seroclearance cupping therapy on the upper back. Marked improvement as regards the scales, itchiness and discoloration was seen in 5 patients with dermatitis, 6 patients with eczema and 4 patients with psoriasis after colon clear. Improvement was much more marked after cupping therapy.